2012
DOI: 10.1007/s10689-012-9532-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Finnish family confirms RHBDF2 mutations as the underlying factor in tylosis with esophageal cancer

Abstract: Tylosis with esophageal cancer (TOC) is a rare familial cancer syndrome inherited in an autosomal-dominant manner and characterized by esophageal cancer susceptibility and hyperkeratotic skin lesions. Two heterozygous missense mutations in the RHBDF2 gene were recently reported to be associated with TOC in three families: a p.Ile186Thr mutation was found in families from the UK and the US and a p.Pro189Leu mutation was detected in a German TOC family. We aimed to validate these novel results in an independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 13 publications
1
52
0
Order By: Relevance
“…Two recent studies indicated that missense mutations in RHBDF2 (p.I186T, p.P189L, and p.D188N) underlie a familial tylosis with esophageal cancer syndrome in families in the United States, United Kingdom, Germany, and Finland (11,42). Based on our results on Rhbdf2 cub mutant mice, we predicted that increased AREG secretion due to dominant N-terminal mutations in RHBDF2 might drive these human pathological changes.…”
Section: N-terminal-truncated Irhom2 Increases Susceptibility To Epitmentioning
confidence: 50%
See 2 more Smart Citations
“…Two recent studies indicated that missense mutations in RHBDF2 (p.I186T, p.P189L, and p.D188N) underlie a familial tylosis with esophageal cancer syndrome in families in the United States, United Kingdom, Germany, and Finland (11,42). Based on our results on Rhbdf2 cub mutant mice, we predicted that increased AREG secretion due to dominant N-terminal mutations in RHBDF2 might drive these human pathological changes.…”
Section: N-terminal-truncated Irhom2 Increases Susceptibility To Epitmentioning
confidence: 50%
“…In the present study, we find that N-terminal-truncated iRhom2 promotes increased AREG production independent of ADAM17 activity, and thereby induces EGFR activation. In particular, the phenotype of Apc Min/+ Rhbdf2 +/cub mice recapitulates the increased susceptibility to epithelial cancers seen in patients with dominant RHBDF2 mutations (11,42). However, Rhbdf2 cub/cub mice did not spontaneously develop tumors, suggesting that the Rhbdf2 cub mutation might not drive cancer development but, instead, might promote tumor growth and progression by creating a conducive environment.…”
Section: Irhom2-areg-egfr Pathway Is Constitutively Active In Some Epmentioning
confidence: 79%
See 1 more Smart Citation
“…HowelYEvans syndrome (tylosis): autosomal dominant condition because of mutation in RHBDF2 gene, which plays a role in epithelial response to injury. The condition is characterized by thickening of the palmaplantar skin (hyperkeratosis) and is associated with increased risk for esophageal cancer (Saarinen et al, 2012). 11.…”
Section: Unique Mutationsmentioning
confidence: 99%
“…TOC patients suffer from PPK, follicular papules, oral keratosis, and up to a 95% lifetime risk of developing oesophageal cancer (Ellis et al, 1994;Hennies et al, 1995;Stevens et al, 1996). TOC results from mutations in a specifi c region of the long N-terminus of the inactive rhomboid protein iRHOM2, encoded by the gene RHBDF2 (Blaydon et al, 2012;Saarinen et al, 2012). iRHOM2 (and its homologue iRHOM1) traffi c ADAM17 from the ER to the Golgi, where the inhibitory pro-domain is cleaved by furin (Adrain et al, 2012;McIlwain et al, 2012).…”
Section: Adam17mentioning
confidence: 99%